2020
DOI: 10.3847/1538-4357/ab7933
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mass Segregation Effect of X-Ray Sources in Globular Clusters. III. Signs of Binary Disruption in M28

Abstract: Using archival Chandra observations with a total effective exposure of 323 ks, we derive an updated catalog of point sources in the bulge globular cluster M28. The catalog contains 502 Xray sources within an area of ∼ 475 arcmin 2 , and more than 90% of these sources are first detected in this cluster. We find significant dips in the radial distribution profiles of X-ray sources in M28, with the projected distance and width of the distribution dip for bright (L X 4.5×10 30 erg s −1 ) X-ray sources are larger t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…On the other hand, we found significant distribution dips for X-ray sources in 47 Tuc, which is consistent with the mass segregation delay of heavy objects in GCs (Cheng et al 2019a). Using the mass segregation effect of X-ray sources as an indicator of cluster dynamical age, we also show that there is evident acceleration effect for cluster dynamical evolution by tidal stripping in Terzan 5 (Cheng et al 2019b) and M28 (Cheng et al 2020). Besides, we found an abnormal deficiency of X-ray sources in the central region (R 1.5 ′ ) of M28 with respect to its outskirts, which indicates that M28 has suffered an early phase of primordial binary disruption within its central region, and that BHS may play an important role in creating and maintaining this peculiar distribution of X-ray sources in M28 (Cheng et al 2020).…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…On the other hand, we found significant distribution dips for X-ray sources in 47 Tuc, which is consistent with the mass segregation delay of heavy objects in GCs (Cheng et al 2019a). Using the mass segregation effect of X-ray sources as an indicator of cluster dynamical age, we also show that there is evident acceleration effect for cluster dynamical evolution by tidal stripping in Terzan 5 (Cheng et al 2019b) and M28 (Cheng et al 2020). Besides, we found an abnormal deficiency of X-ray sources in the central region (R 1.5 ′ ) of M28 with respect to its outskirts, which indicates that M28 has suffered an early phase of primordial binary disruption within its central region, and that BHS may play an important role in creating and maintaining this peculiar distribution of X-ray sources in M28 (Cheng et al 2020).…”
Section: Introductionmentioning
confidence: 73%
“…On the other hand, the threshold value of P B also offers us a criterion to calculate the limiting detection sensitivity across the FoV of ω Cen. The resulting sensitivity maps were found to be very useful in estimating the contribution of cosmic X-ray background (CXB) sources and Galactic interlopers (Cheng et al 2019b(Cheng et al , 2020.…”
Section: Sources Detection and Sensitivitymentioning
confidence: 99%
“…For example, Geller et al ( 2013) and de suggest that, contrary to the effects of mass segregation, the binary fraction in the globular cluster NGC 1818 decreases radially towards the center because binary disruption dominates closer to the core. Cheng et al (2020) discuss a similar competition between mass segregation and binary disruption in the context of the globular cluster M28's X-ray binary population. While N-body simulations are necessary to obtain a comprehensive picture of GC binary demographics over time, based on these calculations, we expect that mass segregation plays a secondary role to evaporation in shaping the distribution of binaries in the GC, in particular the binary fraction as a function of distance from the SMBH.…”
Section: Mass Segregation and Comparison With Globular Clustersmentioning
confidence: 97%
“…Interestingly, spectra of such CVs could be relatively easy to obtain, since crowding should not be a big problem in the outer parts. With respect to observations, Cheng et al (2019a [164]; 2019b [165]; 2020 [166]) recently investigated the phenomenon of mass segregation in the GCs 47 Tuc, Terzan 5 and M28. These authors confirmed that there are some X-ray sources located outside the half-light radii and showed that the radial distribution of X-ray sources in these clusters is bimodal, with features similar to those found in the radial distribution of blue stragglers, they being modulated by mass segregation of primordial binaries.…”
Section: Simulations By Belloni Et Al (2019)mentioning
confidence: 99%